Children's talk about conflict: an exploration of the voices and views of the `Experts': - Hale, Claudia L.; Tardy, Rebecca W.; Farley-Lucas, Bonnie (Discourse & Society, 1995)
The research reported in this paper is an exploration of children's understandings of the concept and experience of interpersonal conflict. Data were gathered at focus group discussions with 7- to 16-year-old children. The analysis which is presented focuses on the children's metaphors of conflict as a place, conflict as an explosion and conflict as betrayal. Children's own descriptions of their experiences and understandings are emphasized. Thus, to the extent possible, what is presented is an examination of children's perspectives/voices as opposed to adult-centered analyses of children's experiences.
4 citations (Crossref) [2023-10-31] Citation Key Alias: pop00192 tex.type: [object Object]
Keywords: betrayal; children's discourse; conflict; dept.com; explosion; fighting; interpersonal conflict; metaphors; place